Perbedaan efektivitas ekstrak kulit apel hijau (Pyrus malus L) 25% dengan larutan xylitol 10% dalam menghambat pertumbuhan bakteri Streptococcus mutans secara in vitro - Hutagalung, Mangatas Halomoan Parluhutan; Tarigan, Susiani (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2019)
One of the most predominant bacteria that cause dental caries is Streptococcus mutans. Streptococcus mutans is a gram-positive bacterium that can metabolize carbohydrates, especially sucrose and creates acid environment in the oral cavity. Streptococcus mutans has two enzyme systems in the cell walls to form two esktraseluler polysaccharides from sucrose. Streptococcus mutans can be treated with medication. One is the green apple skin extract (Pyrus Malus L) 25% to 10% xylitol solution. Green apple skin contains several phytochemicals including quercetin, catechin and chlorogenic acid and xylitol solution containing xylitol can inhibit Streptococcus mutans In Vitro secra. The purpose of this study to determine whether there are differences in the effectiveness of green apple skin extract (Pyrus Malus L) 25% to 10% xylitol solution in inhibiting the growth of bacteria Streprococcus mutans in vitro. The method used is an experimental laboratory research. This study was conducted using a sample of the bacteria Streptococcus mutans. The results of this study indicate that there are significant not differences in inhibiton zone diameter green apple skin extract of 25% 10,042±0,3797 and xylitol solution of 10%. Based on the test results conducted, it is concluded that green apple skin extract (Pyrus Malus L) 25% not differences of Streptococcus mutans bacteria with 10% xylitol solution 9,8±0,3594.